Biocoke from wastewater sludge is an effective substrate for disinfecting Msw polygons and restore soil quality - S. O. Makoev; I. G. Akhmetova (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Wastewater treatment and waste disposal of sorbents obtained from residual biomass. Obtaining biocoke from sludge. Ensuring maximum calorific value of raw materials.METHODS. X-ray phase analysis of ash after burning spent sorbents. Thermogravimetric analysis of biocoke in an oxidizing environment. Elemental analysis evaluation of raw materials and products of municipal solid waste thermal conversion. Experimental analysis of municipal solid waste morphological composition for the municipal district.RESULTS. Completed experimental studies on the analysis of sewage sludge and an assessment on energy and environmental indicators. The substation of partial replacement of fossil fuels by using municipal solid waste in thermal energy generation. Scheme of wastewatertreatment and application of used sorbents as fuel. In order to clarify the calorific value, experiments were made in a calorimetric bomb which showed that biocoke has a lower calorific value of 11.5 MJ/kg. The calorific value of biocoke was obtained according to the data of a thermal analyzer, which is 8–12 MJ/kg and depends both on the type of initial sewage sludge and on the mode of biocoke preparation.CONCLUSION. The obtained results make possible to evaluate the effectiveness of biocoke usage obtained by conversion of sewage sludge for the disinfection of MSW landfills and the impact on restoring soil quality.